1992
DOI: 10.1111/j.1399-3054.1992.tb08779.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exposure to microgravity on the development and structural organisation of plant protoplasts flown on Biokosmos 9

Abstract: Preparatory experiments for the IML-1 (International Microgravity Laboratory) mission to be flown on the Space Shuttle in January, 1992, were performed on a 14 day flight on Biokosmos 9 (Kosmos 2044) in September 1989. The purpose of the experiment was to study the effect of weightlessness on protoplast regeneration. Problems with late access to the space vehicle meant that the newly isolated protoplasts from hypocotyl cells of rapeseed (Brassica napus L. cv Niklas) and suspension cultures of carrot (Daucus ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Narrow polyethylene bags (2 mm in diameter) were used for the cultivation of the protoplasts and mounted in the mid‐axis of the horizontal clinostat. The polyethylene bags are made of the same material as the bags used in space experiments performed by our group (see Rasmussen et al 1992). The protoplasts were cultivated on the clinostat in the dark (25°C) for 5, 24, 48, 72 or 96 h. Exposure of the protoplasts to hyper ‐g (7–10 g ) was done by using a special centrifuge (A. Johnsson, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Narrow polyethylene bags (2 mm in diameter) were used for the cultivation of the protoplasts and mounted in the mid‐axis of the horizontal clinostat. The polyethylene bags are made of the same material as the bags used in space experiments performed by our group (see Rasmussen et al 1992). The protoplasts were cultivated on the clinostat in the dark (25°C) for 5, 24, 48, 72 or 96 h. Exposure of the protoplasts to hyper ‐g (7–10 g ) was done by using a special centrifuge (A. Johnsson, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…Space‐flight experiments have indicated that protoplasts have a reduced production of cellulosic compounds and a decreased frequency of cell divisions under the conditions of weightlessness. In addition, protoplast volume has been observed to increase under micro ‐g conditions (Iversen et al 1992; Klimchuk et al 1992; Rasmussen et al 1992, 1994a,b; Iversen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Gray , Helianthus annuus L. , Lactuca sativa L. (all Asteraceae, eudicots; Merkys & Laurinavichius ; Brown & Chapman ; Halstead & Dutcher ; Rasmussen et al . ; Perbal & Driss‐Ecole ; Tripathy et al . ; Kordyum ; Kiss et al .…”
Section: Introductionunclassified
“…It is in particular the ability to regenerate mature plants from protoplast cultures that makes this experimental system interesting for applications in space exploration. Under micro-gravity conditions, cell wall formation in protoplasts isolated from Brassica napus , Daucus carota , and Solanum tuberosum is significantly delayed compared with the control samples at 1- g (Nedukha et al, 1994; Rasmussen et al, 1994, 1992). In particular, the content of structural components such as cellulose and hemicellulose is reduced whereas pectin is unaltered (Nedukha, 1998; Skagen and Iversen, 2000).…”
Section: Single-cell Systems Useful For Understanding Statolith-indepmentioning
confidence: 99%
“…In these studies, peroxidase activity was measured in the regenerating protoplasts and revealed a decrease in enzyme activity compared to the ground control (Rasmussen et al, 1992). Since peroxidase activity is involved in cell wall metabolism and cross-linking of microfibrils, this reduced activity was proposed to provide a possible explanation for the observed slow-down in cell wall regeneration.…”
Section: Single-cell Systems Useful For Understanding Statolith-indepmentioning
confidence: 99%